دور أدوات استكشاف المعرفة في بناء نظم دينامكية لدعم القرارات الإدارية - الموسى, ياسر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
نقدّم في هذا البحث بنية لنظام ديناميكي لدعم قرارات الإدارة. ويتيح هذا النظام إمكانية الاستفادة من البيانات المخزنة في قواعد بيانات المنظمة واستخدامها في استكشاف معارف جديدة تضاف إلى معارف المنظمة، أو تغيير قواعد معارف النظام بحسب التغييرات التي تطرأ على بيانات المنظمة. ونبين من خلال هذا البحث أيضاً إمكانية تطوير نظم إدارة المعرفة في نظم دعم القرارات الإدارية بإضافة أدوات خاصة لاستخلاص المعرفة، وجعل هذه الأنظمة تعمل ديناميكياً لدعم القرارات الإدارية. In this paper we present a structure for a dynamic system that can be used for management decision support. This system provides the possibility to use the data stored in the organization’s databases and use it to explore a new knowledge which can be added to the existing organization’s knowledge, or changing the system knowledge bases according to the organization’s data changes that might take place. Also, this research will show the possibility of developing knowledge management system in a managerial decision support system by adding special tools to discover knowledge, and consequently drive this system to operate dynamically for the managerial decision support.